The present-day stress field along the Northwest Pacific Wadati-Benioff zone constrained by focal mechanisms of moderate earthquakes - Liu, Chengyu; Liu, Fangbin; Cai, Yin; Ni, Ran; Xu, Xiujie; Li, Guoyi; Hao, Weiduo; Tian, Zhaoyang (Frontiers in Earth Science, 2023)
The present-day stress field in the northwest Pacific Wadati-Benioff Zone (WBZ) has been investigated on the basis of earthquake focal mechanism catalog covering the period from 2012 to 2021. Our catalog contains 201 focal mechanism solutions (Mw 4.0-5.9) compiled from the F-net network along three profiles (southern Kurile trench, central Japan trench and northern Izu-Bonin trench). According to the spatial variations in the stress regimes, we outlined 12 subvolumes for three profiles. Our results present that the maximum compressive stress is, slab-normal in trench-outer rise regions and nearly strike-normal and sub-horizontal in the depth range 0-70 km. At intermediate depths, a two-planar stress pattern is observed (70-200 km) in southern Kurile and central Japan trench WBZ, with the maximum compressive stress closely parallel to the slab in upper plane and slab-normal in lower plane, respectively. However, the southern Kurile trench WBZ exposes an extension stress regime in 200-300 km depth range. At depths below 300 km, northern Izu-Bonin trench WBZ shows a stress regime of pure compression. We infer the dominant forces may be the slab blending in the shallow trench-outer rise regions, slab pull and ridge push at shallow depths, and the slab resistance provided by the mantle to the penetration of the slab at deep depths. Whereas the two-planar stress pattern may be caused by the unbending of the slab, and the unusual stress state along the junction of the trench WBZ at intermediate depths may be influenced by lateral deformation due to increasing slab’s dip.